PENGEMBANGAN BOOKLET PADA MATERI SISTEM PERNAPASAN MANUSIA DI SMA - Nurma Eriani; Kaspul; Bunda Halang (EDUBIOLOCK, 2025)
Currently, most teachers in schools still use textbooks which contain a lot of writing and lack of pictures, making students less interested in learning. This requires new innovations in the learning process, so it is necessary to develop teaching materials in the form of booklet which contain explanations of the material accompanied by attractive images to support the learning process in order to foster students' interest in learning. The aim of this research is to describe the suitability, appropriateness and readability of the Human Respiratory System material booklet in high school. This research and development uses a 4D model which is carried out in 4 stages, namely, 1) Define, 2) Design, 3) Develop and 4) Disseminate with the implementation stage up to Disseminate being limited to the test school. The research subjects were 3 experts and 9 students of class XI MIPA SMA Negeri 11 Banjarmasin. The research instrument is a questionnaire (suitability, appropriateness and readability). Data collection is carried out offline. The results of the research show that the Human Respiratory System teaching material in high school in the form of a booklet that was developed obtained an average suitability score of 4.42 which is classified as "very suitable" which means it is very suitable for the learning objectives, a suitability value of 4.50 which is classified as "very suitable ” which means that it is technically very suitable for use as teaching material and the readability.